Interdisciplinary consensus recommendations for the use of vacuum-assisted breast biopsy under sonographic guidance: first update 2012 = Konsensusempfehlung zu Anwendung und Indikationen der Vakuumbiopsie der Brust unter Ultraschallsicht: erste Aktualisierung 2012 - Hahn, Markus; Sinn, Peter (2012)
Purpose: The vacuum biopsy of the breast under sonographic guidance (VB) was introduced in Germany in the year 2000 and the first consensus recommendations were published by Krainick-Strobel et al. in 2005. Since then, many clinical studies on this technique have been published. The purpose of this publication is to update the consensus recommendations from 2005 regarding the latest literature. Materials and Methods: The consensus statements were the result of two preliminary meetings after the review of the latest literature by members of the Minimally Invasive Breast Intervention Study Group from the German Society of Senology. The final consensus text was review by all members of the working group. The statements listed under results obtained complete acceptance (consensus 100 %). Results: The consensus recommendations describe the indications, investigator qualifications, technical requirements, documentation, quality assurance and follow-up intervals regarding the latest literature. Conclusion: The VB is a safe method for extracting breast tissue for histological workup. The technique allows the resection of breast tissue up to 8 cm3. Besides the diagnostic indications, the method qualifies for a therapeutic resection of symptomatic benign lesions (e. g. fibroadenomas). The technique should be used in specialized breast centers working in a multidisciplinary setup. This paper is an expert’s recommendation for the use of VB under sonographic guidance. It is not formulated as a nationwide guideline.